Using partial participatory GIS in vulnerability and disaster risk reduction in Grenada. (23rd February 2017) - Canevari-Luzardo, Laura; Bastide, Joan; Choutet, Isabelle; Liverman, Diana
Abstract : This paper describes the findings of a novel participatory geographic information systems (PGISs) methodology designed to support vulnerability and disaster risk management (DRM) efforts in small Caribbean communities. The methodology combines community vulnerability mapping with geo-referenced household data through a step-by-step approach to record information on household vulnerability and community hazards. We used "partial" PGIS to demonstrate the benefits of implementing a participatory mapping technique with an external facilitator who undertook the technical geographic information system aspects of the mapping process. Results show that as a tool for knowledge co-production and stakeholder engagement, PGIS can be useful to record local spatial knowledge on vulnerability and hazards whilst supporting the development of risk and vulnerability reduction measures. By helping community members understand and manage vulnerability, this approach has the potential to become an important mechanism to support vulnerability reduction and DRM strategies in small Caribbean communities. Following the approach described in this paper, similar activities can be easily replicated in other parts of the world.